Investigation of Endothelial Cell Density after PreserFlo Implantation Compared to Contralateral Eyes without PreserFlo Implantation – A Retrospective Analysis - Grobshäuser, Ellen; Cunha Vaz Martinho, Antonio; Gatzioufas, Zisis; Hasler, Pascal; Maloca, Peter; Gugleta, Konstantin (Klinische Monatsblätter für Augenheilkunde, 2025)
Background Loss of corneal endothelial cells after glaucoma surgery can lead to corneal decompensation and reduced vision. This loss may be accelerated by drainage implants like PreserFlo, which allow controlled subconjunctival filtration. In a retrospective analysis, we examined its impact on corneal endothelial cell density (ECD).Patients and methods Data from medical records for 94 eyes were retrospectively analyzed. This included 47 PreserFlo-operated eyes and 47 contralateral control eyes. Inclusion criteria were open-angle glaucoma, laser trabeculoplasty as the only prior glaucoma surgery, and a contralateral control eye without any previous glaucoma surgeries and without any relevant diseases. Only standalone procedures and pseudophakic eyes were considered. We included 48 eyes at 2 weeks (24 operated, 24 control eyes), 72 at 3 months (36 each), 34 at 1 year (17 each), and 36 at 3 years (18 each).Results Preoperatively, the 47 eyes that were planned for surgery had a mean ECD of 2141 ± 527 cells/mm², and the 47 control eyes had an ECD of 2114 ± 561 cells/mm². Two weeks postoperatively, ECD decreased by 5.4% in the operated eyes and increased by 1.1% in the control eyes. After 3 months, endothelial cell loss (ECL) was 3.6% (operated) and 1.9% (controls). After 1 year, ECL was 11.7% (operated) and 5.6% (controls); after 3 years it was 7.6% (operated) and 2.9% (controls). No significant differences in ECL dynamics between the operated and control eyes were detected by the analysis of variance.Conclusion Although there was a trend to accelerated ECL in operated eyes compared to controls, this difference was not significant. Overall, the Preserflo procedure appears safe as regards to its influence on endothelial cell count.
Keywords: glaucoma; cornea; endothelial cells; PreserFlo